1995
DOI: 10.1182/blood.v85.12.3510.bloodjournal85123510
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the acute release of tissue-type plasminogen activator from human endothelial cells in vitro and in rats in vivo: evidence for a dynamic storage pool

Abstract: The process of acute release of tissue-type plasminogen activator (tPA) is important in locally speeding up fibrinolysis. Using a sensitive enzyme-linked immunosorbent assay for tPA, we investigated the acute release of tPA from cultured human umbilical vein endothelial cells. The addition of thrombin (0.003 to 3 NIH U/mL) caused the dose-dependent release of noncomplexed, enzymatically active tPA into the medium. The amount of tPA released into the medium by thrombin was similar to the difference in the amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(61 citation statements)
references
References 22 publications
5
56
0
Order By: Relevance
“…Furthermore, plasma levels of t-PA are low (1-9 ng mL )1 ) under normal physiologic conditions [33,34] and become high only after venous occlusion or after the administration of agents that induce its acute secretion from endothelial cells [34]. As isolated blood monocytes and platelets bind t-PA with low affinity (K d values in the range 0.3-0.9 lM) [35,36]) these cells are unlikely to bind t-PA under basal conditions and/or retain it after cell isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, plasma levels of t-PA are low (1-9 ng mL )1 ) under normal physiologic conditions [33,34] and become high only after venous occlusion or after the administration of agents that induce its acute secretion from endothelial cells [34]. As isolated blood monocytes and platelets bind t-PA with low affinity (K d values in the range 0.3-0.9 lM) [35,36]) these cells are unlikely to bind t-PA under basal conditions and/or retain it after cell isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue-type plasminogen activator, t-PA, is the key enzyme initiating the intravascular fibrinolysis (4)(5)(6). t-PA is secreted from the vascular endothelium by two main pathways: a) a basal constitutive secretion of t-PA regulated through the cellular protein synthesis and b) an acute, receptor-mediated short-term release from a storage pool (4,7,8). Circulating t-PA exists in a free, active form and in a complex-bound inactive form (4,7), both of which are eliminated mainly by the liver (10,11).…”
mentioning
confidence: 99%
“…(Meissauer et al, 1991;Alizadeh et al, 1995), should stimulate more detailed studies on the role of t-PA in invasive processes in general. The finding that a significant part of t-PA is cell-associated suggests that, in T-leukemia cells, t-PA is either bound to a cell-surface receptor (Hajjar, 1995) or is present in a t-PA storage granule (Van den Eijnden-Schrauwen et al, 1995) as was observed for human endothelial cells. Which of these possibilities applies and to what extent the cell-associated fraction of t-PA is important for cell migration remains to be established.…”
Section: Discussionmentioning
confidence: 91%